Protected area characteristics that help waterbirds respond to climate warming. Issue 4 (3rd February 2022) - Gaget, Elie; Johnston, Alison; Pavón‐Jordán, Diego; Lehikoinen, Aleksi S.; Sandercock, Brett K.; Soultan, Alaaeldin; Božič, Luka; Clausen, Preben; Devos, Koen; Domsa, Cristi; Encarnação, Vitor; Faragó, Sándor; et al.
Abstract: Protected area networks help species respond to climate warming. However, the contribution of a site's environmental and conservation‐relevant characteristics to these responses is not well understood. We investigated how composition of nonbreeding waterbird communities (97 species) in the European Union Natura 2000 (N2K) network (3018 sites) changed in response to increases in temperature over 25 years in 26 European countries. We measured community reshuffling based on abundance time series collected under the International Waterbird Census relative to N2K sites' conservation targets, funding, designation period, and management plan status. Waterbird community composition in sites explicitly designated to protect them and with management plans changed more quickly in response to climate warming than in other N2K sites. Temporal community changes were not affected by the designation period despite greater exposure to temperature increase inside late‐designated N2K sites. Sites funded under the LIFE program had lower climate‐driven community changes than sites that did not received LIFE funding. Our findings imply that efficient conservation policy that helps waterbird communities respond to climate warming is associated with sites specifically managed for waterbirds. Abstract : Article impact statement : Protected area management and species targets help waterbird communities respond to climate warming inside the Natura 2000 network. Resumen: Las redes de áreas protegidas ayudan a las especies a responder al calentamiento climático. Sin embargo, se sabe muy poco sobre la contribución de las características ambientales y relevantes para la conservación de un sitio a estas respuestas. Investigamos cómo la composición de las comunidades no reproductivas de aves acuáticas (97 especies) en la red (3, 018 sitios) Natura 2000 de la Unión Europea (N2K) cambió en respuesta a los incrementos de la temperatura durante más de 25 años en 26 países europeos. Medimos la reorganización comunitaria con base en series temporales de abundancia recolectadas durante el Censo Internacional de Aves Acuáticas en relación con los objetivos de conservación de los sitios N2K, el periodo de asignación de fondos y el estado del plan de manejo. La composición comunitaria de las aves acuáticas en los sitios con planes de manejo y designados explícitamente para su protección cambió más rápidamente en respuesta al calentamiento climático que en otros sitios N2K. Los cambios comunitarios temporales no se vieron afectados por el periodo de asignación a pesar de una mayor exposición al incremento de la temperatura dentro de los sitios N2K de asignación tardía. Los sitios financiados por el programa LIFE tuvieron menos cambios comunitarios causados por el clima que los sitios que no recibieron este financiamiento. Nuestros hallazgos sugieren que la política de conservación eficiente que ayuda a las comunidades de aves acuáticas a responder al calentamiento climático está asociada con sitios específicamente gestionados para las aves acuáticas.